The Effect of Yeast Dose on Cassava Fermentation Result Manihot utilissima - Ridha Nirmalasari; Ikrima Erma Liani (Universitas Hasanuddin, 2018)
The research is aimed to know the effect of yeast dose on cassava fermentationresult Manihot utilissima, to find the correct yeast dose to give the best fermentationresult and to know the level of people's preference to each yeast dose produced from thefermentation process. The method used is a quantitative research using experimentalmethod and RAL. Result of analysis indicate from some treatments done can be knownthat an organoleptik test of color and flavor give result that F count bigger than F tableso Ho rejected at level of trust 0,05. While an organoleptic test of taste and texture giveresult that F count smaller than F table so Ho accepted at level of trust 0,05. So it can beconcluded that the presence of measurements for the proper dosing of yeast will improvethe quality of tape produced.